Family Development Session Intervention as an Effort to Increase Family Capability - Tuti Alawiyah; Yanti Shantini; Nike Kamarubiani (Universitas Negeri Jakarta, 2025)
ABSTRACT Looking at things through the lens of Amartya Sen's capability theory, this study looks at how the Family Development Session (FDS) program helps family members improve their skills. We employ a literature study as our research method, which entails a theoretical and empirical analysis of reliable sources. Sen's capability theory emphasizes the importance of individual freedom to choose the desired way of life and improve their ability to achieve a dignified life. The FDS program, as a family development initiative, is carried out with the aim of enhancing the capabilities of Program Keluarga Harapan (PKH) beneficiary members who are underprivileged. The results of the literature analysis show that the FDS program has great potential in improving the capabilities of family of hope members through a holistic approach, covering aspects such as health, education, financial management, and participation in community life. The program provides opportunities for family members to acquire the necessary knowledge, skills, and resources to achieve a better life in accordance with their preferences and values. The results of this study reinforce the understanding that the FDS program can be an instrument in enhancing the capabilities of family of hope members, thus enabling them to be more actively involved in society and achieve a more dignified life in accordance with Amartya Sen's vision.